Risk factor analysis for adverse prognosis of the fetal ventricular septal defect (VSD) - Wang Shan; Xia Yuanqing; Zhu Jing; Wu Xi; Guo Huifeng; Wu Yi (BMC, 2023)
Abstract Background Ventricular septal defect (VSD) is the most common subtype of congenital heart disease. In the present study, we aimed to determine whether chromosome aberration was associated with the occurrence of VSD and evaluate the association of VSD size, location and chromosome aberration with adverse outcomes in the Chinese fetuses. Methods Fetuses with VSD and comprehensive follow-up data were included and evaluated retrospectively. Medical records were used to collect epidemiological data and foetal outcomes. For VSD fetuses, conventional karyotype and microarray analysis were conducted. After adjusting confounding factors by using multivariable logistic regression analyses, the association between chromosome variations and VSD occurrence was explored. The association between defect size, location and chromosome aberrations and adverse foetal outcomes was also investigated. Results Chromosome aberration was the risk factor for VSD occurrence, raising 6.5-fold chance of developing VSD. Chromosome aberration, peri-membranous site and large defect size of VSD were significant risk factors of adverse fetal outcome. Chromosome aberrations, including pathogenic copy number variations (CNVs) and variations of uncertain significance (VUS), were both risk factors, increasing the risk of the adverse fetal outcome by 55.9 times and 6.7 times, respectively. The peri-membranous site would increase 5.3-fold risk and defects larger than 5 mm would increase the 7.1-fold risk for poor fetal outcome. Conclusions The current investigation revealed that chromosomal abnormalities, large defects, and the peri-membranous site were all risk factors for poor fetal outcomes. Our study also indicated that chromosome aberration was one of risk factors for the VSD occurrence.